Selectivity and Activity of Benzene-1,2,4-triol and its Dimers as Antimicrobial Compounds Against Xanthomonas citri subsp. citri - Cavalca, Lúcia B.; Atlason, Úlfur Á.; Trofin, Alexandru; Ribeiro, Camila M. [UNESP]; Pavan, Fernando R. [UNESP]; Deuss, Peter J.; Scheffers, Dirk-Jan (Wiley, 2024)
Citrus canker, caused by the bacterium Xanthomonas citri subsp. citri, is one of the main threats to citrus fruit production. Several phenolic compounds active against X. citri have been described in recent years. Benzene-1,2,4-triol is a bio-based phenolic compound that has shown high potential as a scaffold for the synthesis of new anti-X. citri compounds. However, benzene-1,2,4-triol is prone to oxidative dimerization. We evaluated the antibacterial activity of benzene-1,2,4-triol, its oxidized dimers, and analogous compounds. Benzene-1,2,4-triol has a low inhibitory concentration against X. citri (0.05 mM) and is also active against other bacterial species. Spontaneous formation of benzenetriol dimers (e. g. by contact with oxygen in aqueous solution) reduced the antimicrobial activity of benzenetriol solutions. Dimers themselves displayed lower antibacterial activity and where shown to be more stable in solution. Unlike many other phenolic compounds with anti-X. citri activity, benzene-1,2,4-triol does not act by membrane permeabilization, but seems to limit the availability of iron to cells. Benzene-1,2,4-triol is widely recognized as toxic – our results indicate that the toxicity of benzene-1,2,4-triol is largely due to spontaneously formed dimers. Stabilization of benzene-1,2,4-triol will be required to allow the safe use of this compound.
Keywords: Bactericide; Biomass; Citrus canker; Crop protection agents; Dimerization